Analisa Proses Perizinan Usaha Produk Kayu Lapis di PT Anugerah Albasia Abadi Talun Kabupaten Blitar - Andhika Putra Pangestu; Ferida Asih Wilujeng; Putri Cinta Mei (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyzes the business licensing process for plywood products at PT Anugerah Albasia Abadi Talun, Blitar Regency. It aims to identify the processes undertaken, the obstacles encountered, and to provide recommendations. Employing a descriptive qualitative approach and the Triple Bottom Line framework, data was collected through interviews, observation, and documentation studies. The research findings indicate that the company has successfully fulfilled all complex formal licensing requirements, including the Business Identification Number (NIB), Industrial Business License (IUI), Timber Legality Verification Sistem(SVLK) certificate, Environmental Management and Monitoring Efforts (UKL-UPL), and Forest Product Transportation and Trading License (IPHH), demonstrating a commitment to regulatory compliance. Nevertheless, the licensing process is still hampered by the disharmony between the digital Online Single Submission (OSS) system and manual practices, dynamic regulatory changes that are not yet widely disseminated, limited internal human resource capacity, and a lack of harmonization and coordination among government agencies. The Triple Bottom Line analysis reveals that licensing legality supports economic competitiveness and market access, while social aspects are well-established through local job creation and CSR programs. However, environmental management remains administrative and not yet fully performance-based. Therefore, the research recommendations focus on strengthening internal capacity, optimizing the OSS system, developing proactive environmental management, and enhancing continuous community involvement to achieve higher operational efficiency and sustainability